If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-5)=5x-1
We move all terms to the left:
3(x-5)-(5x-1)=0
We multiply parentheses
3x-(5x-1)-15=0
We get rid of parentheses
3x-5x+1-15=0
We add all the numbers together, and all the variables
-2x-14=0
We move all terms containing x to the left, all other terms to the right
-2x=14
x=14/-2
x=-7
| 12/x=3.41 | | 9x+3=15-x | | -(x-5)=-4x-1 | | Y-6/2=3-2y/5*2 | | 12/x=3.41/1 | | 7/x=11/22 | | 3=8z-5 | | x^2+40x-256=0 | | -(x-4)=3x-28 | | 2m/5-1=3 | | (x-453)=0 | | 4x-15=12x-101 | | 3x-2=x+38= | | 5+2(x-1)=×+4(x-3) | | 91=7x13 | | 5v-45=-5(v+5) | | y/2y=5(3+y | | 3(x+3)=8x-41 | | 0.8x-2.6=2.3x+2.1 | | 62=(14y+6) | | 6x-16=8x+5 | | -4(x+5)=0 | | 2z/9+3=6 | | 9×+8=7x+18 | | 12=12^2-4a | | x²+7=23 | | (x+3)²+(x+10)²=70 | | 14x-178=5x-7 | | 3x+40=x-12 | | b7+3=11 | | 9(x-4)=-5.4 | | x+x+8=64 |